Pathogenetic features of endothelial dysfunction at respiratory-cardiac comorbidity - A. Kh. Akhmineeva; O. S. Polunina; I. V. Sevostyanova; L. P. Voronina (Кубанский научный медицинский вестник, 2014)
A correlation analysis to identify the relationship between markers of endothelial dysfunction (coefficient of endothelial function - EFC, type C natriuretic peptide, endothelin-1) and indicators reflecting the activity of inflammation (C - reactive protein, fractalkine) in patients with chronic obstructive pulmonary disease (COPD), bronchial asthma (BA), coronary heart disease (CHD), arterial hypertension (AH) and in patients with comorbidity (COPD+CHD, COPD+AH, BA+ CHD, BA+AH). It was revealed that at comorbid combinations COPD+AG, BA+AG basic mechanism of development of endothelial dysfunction is the activation of chemotactic inflammatory cascade with hyperproduction of fractalkine. C-reactive protein, fractalkine are diagnostic and prognostic markers defeat of endothelium in patients with combinations of COPD+ CHD, BA+CHD.